Personalised therapy in pancreatic carcinoma – a forthcoming opportunity? - Płachta, Iga; Durlik, Marek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2026)
Pancreatic cancer remains the leading cause of cancer-related mortality. Despite overall advancements in oncological treatment, therapeutic approach remains limited, especially for advanced disease. Precision medicine, basing on the patient’s unique characteristics, including environment, lifestyle, genetics, and disease profile, may complete the cancer management. Starting from the current therapeutic algorithms, this review explores the potential role of personalised treatment as a key to improve the outcomes. Molecular classification based on identification of genetic mutations aids better therapy selection in view of the disease heterogeneity. Patient-derived organoids help in adjusting the current treatment standards to specific tumours, assessing the potential treatment efficacy before the introduction of therapy, whereas the mRNA vaccines, as the novel adjuvant approach, may support the achievement of long-term survival. The proposed opportunities could facilitate the treatment strategies, and continued research is essential for improving patient survival rates.